2022
DOI: 10.1136/bmj-2022-071966
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of awake prone positioning in patients with covid-19 related hypoxemic respiratory failure: systematic review and meta-analysis of randomized trials

Abstract: Objective To determine the efficacy and safety of awake prone positioning versus usual care in non-intubated adults with hypoxemic respiratory failure due to covid-19. Design Systematic review with frequentist and bayesian meta-analyses. Study eligibility Randomized trials comparing awake prone positioning versus usual care in adults with covid-19 related hypoxemic respiratory failure. Information sources we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
43
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(51 citation statements)
references
References 38 publications
4
43
0
4
Order By: Relevance
“…“Efficacy of awake prone positioning in patients with covid-19 related hypoxemic respiratory failure: systematic review and meta-analysis of randomized trials” in the style of The BMJ, original article 31…”
Section: Discussionmentioning
confidence: 99%
“…“Efficacy of awake prone positioning in patients with covid-19 related hypoxemic respiratory failure: systematic review and meta-analysis of randomized trials” in the style of The BMJ, original article 31…”
Section: Discussionmentioning
confidence: 99%
“…Feasibility of prone positioning with helmet noninvaisve ventilation has been demonstrated [ 14 ]. A recent systematic review showed that awake prone positioning in patients with acute hypoxemic respiratory failure reduces intubation, although has no impact on mortality [ 15 ].…”
mentioning
confidence: 99%
“…In a linked paper , Weatherald and colleagues (doi:10.1136/bmj-2022-071966) offer the most up-to-date evidence synthesis evaluating the use of awake prone positioning in adults with covid-19 related hypoxaemia,1 finding that awake prone positioning reduced the risk of endotracheal intubation but not mortality. Their systematic review and meta-analysis was performed more than 40 years after a 1976 study observed that prone positioning improved oxygenation in five patients who were mechanically ventilated for acute respiratory distress syndrome (ARDS) 2.…”
mentioning
confidence: 99%
“…In clinical trials with selected populations and increased monitoring, awake prone positioning was found to be safe, with infrequent dislodgement of vascular catheters (2.5%) and skin breakdown or ulcers (0.7%) 1. Given that the definitive reductions were in endotracheal intubation and not mortality, it is worth noting that participants and clinicians could not be masked and this could bias decisions about intubation.…”
mentioning
confidence: 99%